Application Of Islamic Business Ethics Case Study Of Waroeng Steak And Shake A.H Nasution Medan Johor - Suci Rahmida; Muhammad Ikhsan Harahap; Budi Harianto (UNIVED Press, 2023)
This research aims to find out the concept of Islamic business ethics implemented at Waroeng Steak and Shake Branch A.H Nasution Medan. Waroeng Steak and Shake is one of the culinary businesses that underlies every business activity in accordance with the rules of the Al-Quran and Sunnah. This research uses a qualitative method with a phenomenological approach. The data collection methods are interviews, observation and documentation. The data analysis uses data collection, data reduction, data display and data verification. The results of the study can be known and felt by researchers of the existence of different religious nuances compared to the culinary business in general. Waroeng Steak has carried out tasks according to existing SOPs and has implemented Islamic business ethics well using the concepts of Shiddiq, tabligh, amanah and fathanah, namely guaranteeing good and halal ingredients and honesty in transactions, the delivery of da'wah through business, and honesty in financial reports. However, Waroeng Steak and Shake needs to have improved services and spiritual intelligence. So it is recommended to run well the SOP that has been set by the company including the Smile, Salam and Sapa program, in improving services in delivering orders and alternating congregational prayer activities to improve spiritual intelligence